The Role of the Intelkam Unit in Early Detection of Criminal Actions at the Mojokerto Police - Hafizh, Muhammad Arham (Police Studies Review, 2024)
Early detection efforts in taking initial action in the form of prevention of cheating in the jurisdiction of the Mojokerto Police. The problem formulation in this research is 1) what is the role of the intelligence unit in early detection of fraudulent crimes at the Mojokerto Police? 2) What are the factors that influence the implementation of early detection of cheating crimes at the Mojokerto Police? The research approach used is qualitative, while the type of research used is analytical descriptive. Descriptive means describing legal phenomena, systematically factually and accurately regarding the role of the intelligence unit in early detection of fraudulent crimes at the Mojokerto Police, while analytical means providing an assessment of the results of the description without intending to provide general conclusions. The results of the research show that the Mojokerto Police intelligence and security unit has an important role in carrying out its duties in accordance with the reality on the ground in the form of early detection, namely carrying out investigations, namely collecting information and information available to the community using intelligence techniques and tactics. There are several factors that influence the implementation of early detection of fraudulent criminal acts at the Mojokerto Police, including the intelligence capabilities of members, the number of Polri personnel which are not quantitatively sufficient, and very minimal facilities and infrastructure.